2017
DOI: 10.1371/journal.pone.0176216
|View full text |Cite
|
Sign up to set email alerts
|

Dietary DHA/EPA ratio affected tissue fatty acid profiles, antioxidant capacity, hematological characteristics and expression of lipid-related genes but not growth in juvenile black seabream (Acanthopagrus schlegelii)

Abstract: An 8-week feeding trial was conducted to investigate the effects of dietary docosahexaenoic to eicosapentaenoic acid ratio (DHA/EPA) on growth performance, fatty acid profiles, antioxidant capacity, hematological characteristics and expression of some lipid metabolism related genes of juvenile black seabream (Acanthopagrus schlegelii) of initial weight 9.47 ± 0.03 g. Five isonitrogenous and isolipidic diets (45% crude protein and 14% crude lipid) were formulated to contain graded DHA/EPA ratios of 0.65, 1.16, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 85 publications
6
39
0
Order By: Relevance
“…However, in this study, it can be suggested that the insignificant differences in these parameters (SOD, CAT, MDA, TAC) represent a good state of fish while validating that alternative lipids are good potential sources. This means n‐3/n‐6 essentials did not have influences on those antioxidant indicators as previously reported (Jin et al, ; Li et al, ). Speculatively, authors suggest the EPA/DHA ratios were at levels that could neither cause any destruction to the immune oxidative defence system of fish.…”
Section: Discussionsupporting
confidence: 84%
“…However, in this study, it can be suggested that the insignificant differences in these parameters (SOD, CAT, MDA, TAC) represent a good state of fish while validating that alternative lipids are good potential sources. This means n‐3/n‐6 essentials did not have influences on those antioxidant indicators as previously reported (Jin et al, ; Li et al, ). Speculatively, authors suggest the EPA/DHA ratios were at levels that could neither cause any destruction to the immune oxidative defence system of fish.…”
Section: Discussionsupporting
confidence: 84%
“…1 OTUs: Average number of operational taxonomic units. 2 Margalef species richness: d = (S − 1)/log(N) where S is the number of species, and N is the total number of individuals in the sample. 3 Shannons diversity index: H' = − ∑(pi(lnpi)) where pi is the proportion of individuals belonging to the ith species present in the sample.…”
Section: Discussionmentioning
confidence: 99%
“…Part of this bigger picture includes understanding the relationship between dietary LC-PUFA input and output, i.e., the rate and quantity of LC-PUFA synthesis and production. Dietary ratios among the LC-PUFA, such as DHA/EPA and EPA/ARA, are also known to influence the phenotypic response, including growth, lipid metabolism, and LC-PUFA synthesis [ 9 , 10 , 11 ]. Defining, and quantifying, optimal dietary ratios to achieve high muscle tissue storage levels of LC-PUFA would be helpful from a production and consumption standpoint.…”
Section: Introductionmentioning
confidence: 99%